Divergent synthesis of ruthenium alkynyl dendrimers and a two-photon absorption cross-section dendritic effect - Green, K.; Simpson, Peter; Corkery, T.; Cifuentes, M.; Samoc, M.; Humphrey, M. (2012)
Ruthenium alkynyl dendrimers up to second generation in size have been prepared by a divergent route and exploiting Sonogashira coupling. The cubic NLO properties have been examined by wide spectral range fs Z-scan studies, revealing an NLO dendritic effect. The significant increase in NLO properties seen on generation increase is maintained when the coefficients are scaled by the number of metal atoms, the dendrimer molecular weights, or the number of "effective" (delocalizable p) electrons in the dendritic structures. © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.